Effect of processing on the solubility and molecular size of oat β-glucan and consequences for starch digestibility of oat-fortified noodles. (15th March 2022) - Nguyen, Thoa T.L.; Flanagan, Bernadine M.; Tao, Keyu; Ni, Dongdong; Gidley, Michael J.; Fox, Glen P.; Gilbert, Robert G.
Highlights: Noodle-making process and cooking increase solubility of β-glucan. β-Glucan is lost into the cooking water during cooking. Noodle-making process and cooking do not change β-glucan molecular size. Oat-fortified noodle has lower starch digestion rate than wheat noodles. β-Glucan alters microstructure of noodles and reduces the rate of starch hydrolysis. Abstract: White wheat salted noodles containing oats have a slower digestion rate those without oats, with potential health benefits. Oat β-glucan may play an important role in this. Effects of sheeting and shearing during noodle-making and subsequent cooking on β-glucan concentration, solubility, molecular size and starch digestibility were investigated. The levels of β-glucan were reduced by 16% after cooking, due to the loss of β-glucan into the cooking water. Both the noodle-making process and cooking increased the solubility of β-glucan but did not change its average molecular size. Digestion profiles show that β-glucan in wholemeal oat flour did not change starch digestion rates compared with isolated starch, but reduced the starch digestion rate of oat-fortified wheat noodles compared to the control (wheat noodles). Confocal laser scanning microscopy suggests that interaction between β-glucan and protein contributes to the starch-protein matrix and changes noodle microstructure, and thus alters their digestibility.